answer: y= 2x^2+2x-4
steps:
y= (2x+4)(x-1)
*FOIL method* y= (2x^2-2x+4x-4)
*simplify* y= 2x^2+2x-4
Answer:
1.
T mBAC = mB'A'C'
F 2mABC = mA'B'C'
F BC = 2B'C'
T 2XA = XA'
2
D'(-2/3; -1)
E'(-1;1)
F'(1;1)
G'(1;-1)
3
the centre is L(0;-2)
the scale factor is 4
length J'K' = 4JK
the measure of L is equal the measure of L'
<u>the</u><u> </u><u>table</u><u>:</u>
K(4;2) 4 4 16 16 0+16 -2+16 K'(16;14)
Hello!
This question is super easy to me.
![432/2](https://tex.z-dn.net/?f=432%2F2)
![Answer---> =216](https://tex.z-dn.net/?f=Answer---%3E%20%3D216)
![216*2=432](https://tex.z-dn.net/?f=216%2A2%3D432)
![432/216=2](https://tex.z-dn.net/?f=432%2F216%3D2)
Hope this helps!
Thank you for posting your question at here on Brainly.
-Charlie
Answer is c
use pythagorean
a^2 + b^2 = c^2
8^2+15^2= c^2
289=c^2
sqrt both sides
c=17
BC=17
Answer:
4 hours and 24 minutes
Step-by-step explanation: